Sintesa Fluorinated Tin Oxide (FTO) Menggunakan Prekursor Ramah Lingkungan Dan Penambahan Graphene Dengan Metode Deposisi Spray Coating Untuk Aplikasi Material Konduktif Transparan - Rino Rinaldi; Amun Amri; Khairat Khairat (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Fluorine doped tin oxide (FTO) films were fabricated on a glass substrate by a spray coating deposition methode. Non-toxic SnF2 was used as fluorine source to replace toxic HF or NH4F. Effect of SnF2 content, 0 – 10 mol% and 115 ppm graphene as comparison to the fluor content on the substrate, on structure, electrical resistivity, optical transmittance of the films and morfology were investigated using X-ray diffraction (XRD), Multimeter, UV–vis spectra and Scanning Electron Microscopy (SEM). Structural analysis revealed that the films are amorf with crystal structure. Grain size varies from 501 nm - 175 nm with increasing fluorine concentration, which in fact critically impacts resultant electrical and optical properties. The 300 °C-annealed FTO film containing 10 mol% SnF2 shows the lowest electrical resistivity 14,1 x 10-4 Ωcm, on 5x deposition repeat, optical transmittance 86,4% on 0 mol% SnF2 with once deposition repeat. The highest figure of merit 0,0453 x 104 Ω-1cm-1 which is used for standart of best quality of transparent conductive oxide (TCO). Because of the promising electrical and optical properties, F-doped thin films prepared by this green process are well-suited for use in all aspects of transparent conducting oxide.Keywords: Fluorine doped tin oxide (FTO) films, Transparent conducting oxide (TCO), Sol–gel dip-coating, Electrical resistivity, Optical properties, Figure of merit